CORPUS LINGUISTIC-SEMANTIC BASED APPROACH: REVEALING ROHINGYA’S ISSUE THROUGH NOMINALIZATION AS GRAMMATICAL MEANING IN BBC NEWS AND THE JAKARTA POST - Yogi Setia Samsi (KREDO : Jurnal Ilmiah Bahasa dan Sastra, 2019)
AntPConc is the software that facilitates an unlimited data recognizing the frequency and collocation in order to get categorization of its context. Solidarity issue is concerned by BBC News and the Jakarta Post in delivering Rohingya issues. It is qualitatively aimed to identify the representation of Rohingya’s issue through grammatical meaning in both of media. As limitation, I employed the analysis as van Leeuwen framework (2008) and semantically (Saeed: 2016). To comprehend the result, the data is obtained in a week period that inputted to AntPconc. The data can identify representational meaning of Rohingya’s issue specializing grammatical meaning through frequency and collocation. The findings reveal that both of media have high solidarity toward Rohingya issues. Even though, BBC News is more explicit about raising the actor. Moreover, corpus linguistic also has the contribution to CDA-semantic study especially recontextualization meaning.